Conditional deletion of mTOR discloses its essential role in early B‐cell development. Issue 4 (29th December 2021) - Zhang, Shuling; Dubois, Wendy; Feng, Xingmin; Nguyen, Joe T.; Young, Neal S.; Mock, Beverly A.
Abstract: Mechanistic target of rapamycin (mTOR) is a serine‐threonine kinase and central regulator of cell growth, differentiation, and survival. mTOR is commonly hyperactivated in a diverse number of cancers and critical roles for mTOR in regulating immune cell differentiation and function have been demonstrated. However, there is little work investigating the roles of mTOR in early B‐cell development. Here we demonstrate that conditional disruption of mTOR in developing mouse B cells results in reduced pre‐B‐cell proliferation and survival, as well as a developmental block at the pre‐B‐cell stage, with a corresponding lack of peripheral B cells. Upon immunization with NP‐CGG antigen, mice with Mtor conditional disruption in early B cells lost their ability to form germinal centers and produce specific antibodies. In competitive BM repopulation assays, donor BM cells from conditional knock‐out mice were completely impaired in their ability to reconstitute B cells. Our data reveal the essential role of mTOR in early pre‐B‐cell development and survival.